La Montagne dans l’œuvre de quelques écrivains libanais d’expression anglaise - Jacqueline Jondot (Anglophonia)
Lebanese writers in the English language represent their mountains in an ambivalent manner: they use western aesthetic concepts (sublime, picturesque) while setting their representation in an Eastern context of ideological reappropriation of their land, focusing on its cultural and human occupation with a strong opposition between mountain and city dwellers. The mountain is seen as an ambivalent paradise, both a symbol of innocence and of lawlessness. This series of oppositions is a metaphor for the in-betweennness of these authors